2004
DOI: 10.1017/s0004972700034493
|View full text |Cite
|
Sign up to set email alerts
|

On two open problems about strongly clean rings

Abstract: A ring is called strongly clean if every element is the sum of an idempotent and a unit which commute. In 1999 Nicholson asked whether every semiperfect ring is strongly clean and whether the matrix ring of a strongly clean ring is strongly clean. In this paper, we prove that if R = {m/n 6 Q : n is odd}, then M 2 (R) is a semiperfect ring but not strongly clean. Thus, we give negative answers to both questions. It is also proved that every upper triangular matrix ring over the ring R is strongly clean.Througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…For example, the matrix ring ‫ލ‬ 2 ‫ޚ(‬ (2) ) is not strongly clean. This fact was observed by Sánchez Campos [12] and by Wang and Chen [13] independently (answering two questions of Nicholson in [11]). When is the matrix ring over a strongly clean ring still strongly clean?…”
Section: Introductionsupporting
confidence: 53%
“…For example, the matrix ring ‫ލ‬ 2 ‫ޚ(‬ (2) ) is not strongly clean. This fact was observed by Sánchez Campos [12] and by Wang and Chen [13] independently (answering two questions of Nicholson in [11]). When is the matrix ring over a strongly clean ring still strongly clean?…”
Section: Introductionsupporting
confidence: 53%
“…Nicholson [15] proved that any strongly π-regular element is strongly clean by establishing the following results: for α ∈ end(M ), α is strongly π-regular if and only if there exist α-invariant submodules P and Q such that M = P ⊕ Q, α| P is an isomorphism and α| Q is nilpotent; and α is strongly clean if and only if there exist α-invariant submodules P and Q such that M = P ⊕ Q, α| P and (1 − α)| Q are isomorphisms. Some other notable results on strongly clean rings can be found in [1,2,3,4,13,16,17], etc.…”
Section: Introductionmentioning
confidence: 79%
“…In 2004, Wang and Chen [16] proved that there exists a commutative local ring R such that M 2 (R) is not strongly clean, which answered a question raised by Nicholson in [15]. This motivated many authors studied strong cleanness of matrix rings over local rings ([2, 3, 4, 12, 13, 17]).…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez Campos [40] and Wang-Chen [42] found that M 2 (Z (2) ) is not strongly clean where Z (2) is the localization of the ring of integers Z at the prime ideal (2) = 2Z. Local rings are semiperfect, so M 2 (Z (2) ) is semiperfect but it is not strongly clean.…”
Section: Clean Rings Vs Strongly Clean Ringsmentioning
confidence: 99%